(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Women entrepreneurs are contributing more things to the success of the Indian economy. They are very much helpful in shaping and redefining the working environment, networks, financial institutions and culture of the people. Women are very much skilled and knowledgeable, their interest and performance in business and a motivating desire are some of the reasons for the women entrepreneurs to run an industries. These enterprises range from corner shops to venture-funded startups. Objectives: To analyze the demographic factors of women entrepreneurs and analyze how the factors influence women to become entrepreneurs with special reference to small and medium enterprises, Coimbatore District, Tamil Nadu. Methodology: primary and secondary data collection method have used in the study. Questionnaire method was used for the data collection. 300 sample respondents are selected in Coimbatore District. The sources of secondary data include data from Government reports, research papers, journals, magazines, newspapers, books and internet sources. For analyzing the data and interpreting results, the statistical tools Simple Percentage, KMO measure, Barlett’s test, Cronbatch’s reliability test, Factor analysis and multiple regressions have been used. Result: Hard work, self confidence, Intelligence, better quality of products, business selection and Involvement are considered to be the most significant elements give the success to the women entrepreneurs.